MassHog: Weight-Sensitive Occupant Monitoring for Pig Pens using Actuated Structural Vibrations - Jesse Codling; Amelie Bonde; Yiwen Dong; Siyi Cao; Akkarit Sangpetch; Orathai Sangpetch; Hae Young Noh; Pei Zhang (My University, 2021)
In the swine livestock industry, weight tracking is commonly used to track health and growth of pigs. This is especially crucial during the farrowing period, where mother sows and their newborn piglets are housed together to facilitate nursing. Existing weight measurement methods, however, either provide only sporadic snapshots or have scalability and reliability issues in the harsh environment of industrial farms. This paper presents MassHog, a multi-layered system for ubiquitous weight measurement in harsh environments, such as pig pens, using structural vibrations. MassHog combines an existing sensor concept with actuated vibrations to weigh both piglets and adult hogs together. We evaluate the components of this system through testing deployments, including at real-world operating pig farms. Preliminary results show less than 2 kg mean absolute error for adult hogs.
Keywords: Animal Behavior and Welfare Studies; Food Supply Chain Traceability; Milk Quality and Mastitis in Dairy Cows